Burden syndrome and coping strategies in caregivers of pediatric cancer patients - Reyna-García, Paola Daniela (2021)
Objective: Pediatric cancer caregivers will encounter circumstances that will challenge their personal resources to face the diverse demands of care. Therefore, the objective of the study was to determine the relationship between burden syndrome and coping strategies in caregivers of pediatric cancer patients. Method: 93 main caregivers of pediatric cancer patients participated (69.9% women, 30.1% men, mean age = 37.20 years, SD = 11.32), selected in a non-probabilistic way. The Caregiver Burden Scale and the COPE-28 Questionnaire were applied. Correlational and comparative statistics were used for data analysis. Results: The results indicate the presence of significant and inverse correlations that vary between r =-.25 and r =-.56. However, no significant association was found between the dimensions of caregiver burden and substance use. On the other hand, those caregivers who use poorly adaptive strategies are more likely to generate overload in relation to their role, influencing their personal, family and social life. Conclusion: There is a significant relationship between overload syndrome and coping strategies. In addition, significant differences in overload are identified according to the place of origin and the hours dedicated to care.